+0  
 
+1
38
1
avatar+41 

Hello!

Im struggling with finding the solutions for: \(x^4+2x^2-3=0\)

 

Thankfull for help :D

kilander  Nov 21, 2017

Best Answer 

 #1
avatar
+2

Solve for x:
x^4 + 2 x^2 - 3 = 0

Substitute y = x^2:
y^2 + 2 y - 3 = 0

 

The left hand side factors into a product with two terms:
(y - 1) (y + 3) = 0

 

Split into two equations:
y - 1 = 0 or y + 3 = 0

 

Add 1 to both sides:
y = 1 or y + 3 = 0

 

Substitute back for y = x^2:
x^2 = 1 or y + 3 = 0

 

Take the square root of both sides:
x = 1 or x = -1 or y + 3 = 0

 

Subtract 3 from both sides:
x = 1 or x = -1 or y = -3

 

Substitute back for y = x^2:
x = 1 or x = -1 or x^2 = -3

 

Take the square root of both sides:
x = 1    or    x = -1    or    x = i sqrt(3)    or    x = -i sqrt(3)

Guest Nov 21, 2017
Sort: 

1+0 Answers

 #1
avatar
+2
Best Answer

Solve for x:
x^4 + 2 x^2 - 3 = 0

Substitute y = x^2:
y^2 + 2 y - 3 = 0

 

The left hand side factors into a product with two terms:
(y - 1) (y + 3) = 0

 

Split into two equations:
y - 1 = 0 or y + 3 = 0

 

Add 1 to both sides:
y = 1 or y + 3 = 0

 

Substitute back for y = x^2:
x^2 = 1 or y + 3 = 0

 

Take the square root of both sides:
x = 1 or x = -1 or y + 3 = 0

 

Subtract 3 from both sides:
x = 1 or x = -1 or y = -3

 

Substitute back for y = x^2:
x = 1 or x = -1 or x^2 = -3

 

Take the square root of both sides:
x = 1    or    x = -1    or    x = i sqrt(3)    or    x = -i sqrt(3)

Guest Nov 21, 2017

8 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details